Fibroblast-like Synoviocytes – Actors in Osteoimmunology - Beckmann, Denise; Korb-Pap, Adelheid; Wehmeyer, Corinna (Osteologie, 2021)
Rheumatoid arthritis (RA) is an immune mediated inflammatory disease (IMID), characterized by chronic inflammation and irreversible bone loss. Studies have shown that fibroblast-like synoviocytes (FLS), a key cell population in the pathogenesis of RA, have an impact on balancing bone-forming osteoblasts and bone-destroying osteoclasts towards joint damage. Once activated, RA-FLS are able to destroy cartilage and subchondral bone through the release of RANKL, members of the metalloproteinase family and many more cytokines, chemokines and growth factors. Additionally, RA-FLS are responsible for the perpetuation and chronicity of the disease due the interaction with immune cells supporting the influx of T and B lymphocytes, monocytes, macrophages neutrophils and dendritic cells from the blood stream into the inflamed synovial tissue. In this review we highlight the direct and indirect impact of synovial fibroblasts in RA on joint damage and disease progression. Moreover, we describe mechanisms of synovitis and regulators of bone homeostasis in further inflammatory joint diseases such as ankylosing spondylitis (AS) and psoriatic arthritis (PsA) and compare them to RA.
Keywords: osteoimmunology; bone remodelling; fibroblast-like synoviocytes; RA